Equity and quality? : challenges for early childhood and primary education in Ethiopia, India and Peru - Woodhead, Martin; Ames, Patricia; Vennam, Uma; Abebe, Workneh; Streuli, Natalia (Amsterdam, 2017)
Young Lives, An International Study of Childhood Poverty, Department of International Development, University of Oxford.